PENGUATAN MOTIVASI SHALAT DAN KARAKTER PESERTA DIDIK MELALUI PENDEKATAN PEMBELAJARAN KONTEKSTUAL PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM - Akhmad Fadli (Tarunaedu: Journal of Education and Learning, 2023)
Research conducted at Kawung 2 Middle School Surabaya. In this research, a sample of 32 students was taken from a population of 182 students from SMP Kawung 2 Surabaya. The method used is a descriptive method, which aims to describe the facts and the relationship between the independent variables (X1) and (X2) and the dependent variable (Y). The results of regression and correlation tests show that there is an influence of contextual learning methods in Islamic Religious Education (PAI) on strengthening prayer motivation, strengthening student character, and also a combined influence on prayer motivation and student character. A contextual approach to PAI learning in schools seems to provide significant benefits. This is because this approach helps students to understand PAI better and feel its connection to their daily lives. Several findings that can be drawn from this research include: The Influence of Contextual Learning Methods on Motivation for Prayer: Research shows that the use of contextual learning methods in PAI can increase students' motivation to perform prayers. This may be because students can better understand the importance of prayer in the context of their daily lives. The Influence of Contextual Learning Methods on Strengthening Character: Apart from prayer motivation, contextual learning methods also have a positive impact on strengthening students' character. This can include enhancing moral values, ethics, and other positive attitudes related to religion. This research provides valuable insight into the importance of a contextual approach in PAI learning in schools to motivate students and strengthen their character. The results of this research can be a basis for developing a better and more effective PAI curriculum in the future.